1990
DOI: 10.1243/pime_proc_1990_204_005_01
|View full text |Cite
|
Sign up to set email alerts
|

Transient Temperature Distribution in Arc Welding of Finite Thickness Plates

Abstract: This paper introduces a new analytical solution to predict the transient temperature distributions in a finite thickness plate during arc welding. This analytical solution is obtained by solving a transient three-dimensional heat conduction equation with convection boundary conditions at the surfaces of the weldment. The heat source due to electric arc is assumed to take a travelling Gaussian distribution. T o prove the validity of the model, a series of G T A bead-on-plate welding were performed on a medium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…In the analytical solutions, the influence of phase transformation heat (both solid and liquid) is generally ignored, thermo-physical properties of the material are assumed to be independent of temperature, and only the conduction effect is taken into consideration (the radiation phenomenon and the gravity field are omitted), also Joule heat (for electric arc welding) is omitted [6][7][8][9][10][11][12][13][14][53][54][55][56][57][58]. Such assumptions were also adopted in this work.…”
Section: The Analytical Description Of the Temperature Field During Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analytical solutions, the influence of phase transformation heat (both solid and liquid) is generally ignored, thermo-physical properties of the material are assumed to be independent of temperature, and only the conduction effect is taken into consideration (the radiation phenomenon and the gravity field are omitted), also Joule heat (for electric arc welding) is omitted [6][7][8][9][10][11][12][13][14][53][54][55][56][57][58]. Such assumptions were also adopted in this work.…”
Section: The Analytical Description Of the Temperature Field During Mmentioning
confidence: 99%
“…Na and Lee [5] used an annular heat source where the intensity of the heat flux within the center of the arc welding was determined according to the parameter defined as the radius at which the intensity of the arc power was 5% of the maximum intensity. Bo and Cho [6] derived an analytical solution for transient temperature field in finite thickness plate during single-pass arc welding, assuming Gaussian distribution of heat source. An analytical solution for temporary temperature field of fillet weld has been presented by Jeong and Cho [7] and wasapplied by Fassani and Trevisan [8] to compare the thermal cycles during multi-pass gas metal arc welding (GMAW) which was computed for Rosenthal's models of point heat sources and one-dimensional (1D) Gaussian.…”
Section: Introductionmentioning
confidence: 99%
“…The model of double ellipsoidal, three-dimensional heat source was first introduced by Goldak et al [1]. Since then many researchers have tried to determine the temperature field closest to real distribution using analytical methods [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…They were shown that the convective heat transfer is more effective than radiation in temperature calculations; therefore the radiation can be neglected. Boo and Cho (1990) studied a model to obtain the transient temperature distributions in a finite thickness plate by solving a transient three-dimensional heat conduction equation with convection boundary conditions at the surfaces of the weldment during arc welding. In 1984, the finite difference method has been introduced for stationary and axisymmetric GTAW process with a moving boundary by Oreper and Szekely (1984).…”
Section: Introductionmentioning
confidence: 99%